The Application Of Deaf Children Language Ability Development Of 3-5 Years Old Children - Wantoro, Wantoro; Diana, Diana; SP, Yuli Kurniawati (Indonesian Journal of Early Childhood Education Studies, 2014)
Descriptive Study of the Application of Deaf Children Language Development in TLO (Taman Latihan dan Observasi) Class in Semarang State Special School. Faculty of Education. Semarang State University. Indonesia. The Application of deaf children language ability development is a teaching-learning activity focusing on deaf children language acquisition through approaches, methods and media adapted to the children condition and needs. The research aims to 1) describe deaf children language development, 2) explain the application of deaf children language ability development in TLO (Taman Latihan dan Observasi) class in Semarang State Special School, 3) explain push-pull factors of the application of deaf children language ability development in TLO (Taman Latihan dan Observasi) class in Semarang State Special School. The research employed a qualitative descriptive method to understand the phenomenon happened by the research subjects, namely the language they possess, and push-pull factors of deaf children language ability. The subjects of the research are deaf students at the age of 3-5 in the TLO class of Semarang State Special School. The data of the research were collected by observation, interview, and documentation. They were analyzed by data reduction, data presentation, verification, and conclusion. The results show that most of all deaf children in TLO class were cried at post delivery as normal do. The fact that they have no stimulation response is a symptom their parents observe. Therefore, the push-pull factor here is the active role of the parents. Hence, there are three conclusions according to the research, namely the cry of deaf children at post delivery as normal do, heart to heart approach done by teachers and the active role of the parents in deaf language development. It is suggested that the teachers are expected to be more creative to conduct teaching activity. In addition, the community support is needed while government and education department formulate learning curriculum for special need children. As for the writer, the research is expected to analyze lesson plan.How to citeWantoro, W., Diana, D., & SP, Y. (2014). The Application Of Deaf Children Language Ability Development Of 3-5 Years Old Children. Indonesian Journal Of Early Childhood Education Studies, 3(2), 134-138. doi:10.15294/ijeces.v3i2.9487